High performance recyclable poly(Butyleneterephthalate)/ organomontmorillonite nanocomposites. - Chow, Wen Shyang (Universiti Sains Malaysia, 2007)

(untitled)
3wt% of organo-montmorillonite (OMMT) was incorporated into poly(butylene terephthalate) (PBT) by using melt intercalation method. The PBT/OMMT nanocomposites were produced by using twin screw extrusion followed by injection molding.